2005
DOI: 10.1590/s0101-20612005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da luz e da temperatura de congelamento sobre a estabilidade das antocianinas da pitanga roxa

Abstract: -INTRODUÇÃOFrente a atual tendência mundial em usar pigmentos naturais como corantes para alimentos, ênfase tem sido dado a busca de fontes economicamente viáveis. Neste contexto, destacam-se as antocianinas, compostos fenólicos derivados do cátion favilium, pertencentes ao grupo dos flavonóides, largamente distribuídas na natureza, que conferem a muitos vegetais as várias nuanças de cores entre laranja, vermelho e azul [8]. O interesse por estes pigmentos decorre também de evidências relacionadas ao seu poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
2
7
0
6
Order By: Relevance
“…The highest cyanidin concentrations were detected in Guarani and Caingangue cultivars (about 150 mg.100 g -1 ), values higher than those detected for domestic and wild species grown in China (1-118 mg.100 g -1 ) (DEIGHTON et al, 2000). Also, data shown for blackberry fruits are superior to anthocyanin contents found in other red fruits, such as strawberry (30 to 60 mg.100 g -1 , CORDENUNSI et al, 2003), purple Surinam cherry (16.23 mg.100 g -1 , LIMA et al, 2005) or acerola (3.79 to 59.74 mg.100 g -1 , LIMA et al, 2003).…”
Section: Resultsmentioning
confidence: 80%
“…The highest cyanidin concentrations were detected in Guarani and Caingangue cultivars (about 150 mg.100 g -1 ), values higher than those detected for domestic and wild species grown in China (1-118 mg.100 g -1 ) (DEIGHTON et al, 2000). Also, data shown for blackberry fruits are superior to anthocyanin contents found in other red fruits, such as strawberry (30 to 60 mg.100 g -1 , CORDENUNSI et al, 2003), purple Surinam cherry (16.23 mg.100 g -1 , LIMA et al, 2005) or acerola (3.79 to 59.74 mg.100 g -1 , LIMA et al, 2003).…”
Section: Resultsmentioning
confidence: 80%
“…In this study, the half-life time of the purified anthocyanins exposed to light was lower than the crude anthocyanins extract of purple Surinam cherry (948h; 39 days) in a study conducted by Lima, Mélo and Lima (2005). The greatest light sensitivity of purified anthocyanins, when compared to a crude extract solution, can be justified by the non-formation of complexes with other constituents of the extract (such as flavonoids), since they could act as copigments, promoting color stabilization (CLIFFORD, 2000;MANACH et al, 2004).…”
mentioning
confidence: 57%
“…However, all extracts protected from light showed a remarkably higher half-life than the extracts exposed to light. Lima et al (2005) observed that the anthocyanin extracts from purple cherry showed greater stability when protected from light. Bąkowska et al (2003) found that the heating and UV irradiation affect negatively the stability of anthocyanins.…”
Section: Bioactive Compounds and Rsm Modelingmentioning
confidence: 99%